Pengembangan Buku Saku Digital Berbasis Android Mata Pelajaran PPKn Kelas VII SMP - Larasati, Dyah Eka (Universitas Negeri Malang, 2022)
This study aimed to produce an Android-based digital pocketbook on the subjects of Pancasila and Citizenship Education for grade 7th Junior High School that was feasible and effective. This study followed the research and development stages of ADDIE, including analysis, design, development, implementation, and evaluation. The test subjects used in this study were students of grade 7th Bhakti Junior High School in Malang. The validity test results of material experts obtained a score of 98, media experts were 92, and linguists were 93. Based on small-group trials, the questionnaire filling data were obtained by students with a score of 96 and teachers at 97, while the large group trial obtained a score student response is 97. An Android-based digital pocketbook in the subjects of Pancasila and Citizenship Education for grade 7th Junior High School, especially on the material for the formulation and stipulation of Pancasila as the basis of the state, could be categorized as feasible effective for use as a digital learning medium.